Vascular Characteristics of Treatment-resistant and -responsive Actinic Keratosis Identified with Dynamic Optical Coherence Tomography - Gabriella Fredman; Merete Haedersdal; Peter A. Philipsen; Flemming Andersen; Peter Bjerring; Stine R. Wiegell; Gavrielle Untracht (Medical Journals Sweden, 2024)
Treatment-resistant actinic keratosis (AK) is of concern in clinical practice, often requiring retreatment. Microvascular assessments might help differentiate treatment-resistant from treatment-responsive AKs, enabling targeted treatment. Using dynamic optical coherence tomography, AK vascularization was investigated following daylight photodynamic therapy, comparing treatment-resistant with cleared AKs. AKs on face/scalp were graded according to the Olsen Classification Scheme and scanned with dynamic optical coherence tomography pre-treatment, and 3- and 12-months post-treatment. Employing dynamic optical coherence tomography, total vessel length, mean vessel length, mean vessel diameter, vessel area density, and branchpoint density were quantified. Thirty-eight patients with 62 AKs were enrolled, including 37 AK I, 18 AK II, and 7 AK III. Treatment-resistant AKs displayed a trend toward intensified vascularization compared with cleared AK at baseline (AKs I, II), suggested by higher total vessel length (median 144.0, IQR 104.3-186.6) and vessel area density (median 27.7, IQR 18.4-34.2) than in cleared AK (median 120.9, IQR 86.9-143.0 and median 22.9, IQR 17.3-26.8). Additionally, vascularization in treatment-resistant AK I-II appeared disorganized, with trends toward shorter mean vessel length (median 151.0, IQR 138.5-167.5) and increased branchpoint density (median 3.2, IQR 2.3-3.8) compared with cleared AK (median 160.0, IQR 152.0-169.3 and median 2.6, IQR 2.2-3.0). These findings suggest that dynamic optical coherence tomography holds potential to identify treatment-resistant AKs.